The pyrophilic primate hypothesis. Issue 2 (4th March 2016) - Parker, Christopher H.; Keefe, Earl R.; Herzog, Nicole M.; O'connell, James F.; Hawkes, Kristen
Abstract : Members of genus Homo are the only animals known to create and control fire. The adaptive significance of this unique behavior is broadly recognized, but the steps by which our ancestors evolved pyrotechnic abilities remain unknown. Many hypotheses attempting to answer this question attribute hominin fire to serendipitous, even accidental, discovery. Using recent paleoenvironmental reconstructions, we present an alternative scenario in which, 2 to 3 million years ago in tropical Africa, human fire dependence was the result of adapting to progressively fire‐prone environments. The extreme and rapid fluctuations between closed canopy forests, woodland, and grasslands that occurred in tropical Africa during that time, in conjunction with reductions in atmospheric carbon dioxide levels, changed the fire regime of the region, increasing the occurrence of natural fires. We use models from optimal foraging theory to hypothesize benefits that this fire‐altered landscape provided to ancestral hominins and link these benefits to steps that transformed our ancestors into a genus of active pyrophiles whose dependence on fire for survival contributed to its rapid expansion out of Africa.